Development of “No Anemia No Stunting” (Si NaNing) Modules and Application in Efforts to Prevent Stunting in Archipelago Regions - Aminin, Fidyah; Kristianto, Jusuf; Rianda, Dewi Puspa; Haryadi, Haryadi; Cintiani, Jeni Cesi (Poltekkes Kemenkes Jakarta III, 2022)
The average prevalence of stunting toddlers in Indonesia from 2005 to 2017 is 36.4%. Incidence of stunting toddlers (short) is a major nutritional problem faced by Indonesia. Stunting cases in the Riau Islands reached 24 percent of the number of babies born in 2018. One of the causes of stunting is the lack of nutrients fulfilment during pregnancy, including anemia in pregnancy. Currently, there is no media module and application for stunting prevention health promotion. The purpose of the study was to determine the effectiveness of the